2010
DOI: 10.1002/ase.158
|View full text |Cite
|
Sign up to set email alerts
|

Resilience does not predict academic performance in gross anatomy

Abstract: Few studies have evaluated resilience in an academic environment as it relates to academic success or failure. This work sought to assess resilience in regular and remedial students of gross anatomy during the first and second semesters of medical school and to correlate this personal trait with academic performance. Two groups of students were compared: the first group included first-year medical students in the regular course, and the second group included first-year medical students who did not pass the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
13
3
Order By: Relevance
“…The seven sociodemographic variables examined were not found to be significant predictors of the CD-RISC-25 score. This aligns with other work in Mexican medical students (Elizondo-Omaña et al, 2010), South African physicians (Rossouw et al, 2013), and in the broader U.S. population (Connor and Davidson, 2003), where no differences in mean CD-RISC-25 score were identified by the sociodemographic factors studied. Although they used the Brief Resilience Scale rather than the CD-RISC-25, Porter et al (2018) also did not find associations between the resilience level and demographics of U.S. family medicine programme directors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The seven sociodemographic variables examined were not found to be significant predictors of the CD-RISC-25 score. This aligns with other work in Mexican medical students (Elizondo-Omaña et al, 2010), South African physicians (Rossouw et al, 2013), and in the broader U.S. population (Connor and Davidson, 2003), where no differences in mean CD-RISC-25 score were identified by the sociodemographic factors studied. Although they used the Brief Resilience Scale rather than the CD-RISC-25, Porter et al (2018) also did not find associations between the resilience level and demographics of U.S. family medicine programme directors.…”
Section: Discussionsupporting
confidence: 88%
“…For example, research involving Chinese (Peng et al, 2012), Canadian (Rahimi et al, 2014), and U.S. (Houpy et al, 2017) Chan L, Dennis A MedEdPublish https://doi.org/10.15694/mep.2019.000020.2 medical students found male students as having statistically higher resilience scores than females. Whereas, Elizondo-Omaña et al (2010) did not observe such differences in resilience scores by gender in Mexican medical students. For medical educators, Porter and colleagues (2018) found no associations between the resilience level of U.S. family medicine programme directors and their demographic background, including gender.…”
Section: Resilience In Medical Educationcontrasting
confidence: 57%
“…8,9,45 Second, our students' perceived stress scores were higher than population data (stress scale score of 19.2 overall in our students vs 14.2 for ages 18-29 and 13.0 for ages 20-44 in the general population) 43 , as well as marginally higher than another Canadian medical student population cohort (17 for females and 15 for males). 46 Furthermore these higher perceived stress scores occurred in the context of relatively low resilience scores compared with population data (resilience scale score of 71.2 in our respondents vs 80 for another first year medical student cohort, 40 80.4 for general population, 71.8 for outpatient primary practice setting and 68.0 for outpatient psychiatry setting). 47 We should hope instead that resilience, defined as the capacity to respond to stress in a healthy way such that goals are achieved at minimal psychological and physical cost, 48 could be bolstered during times of stress in order to prevent burnout.…”
Section: Discussionmentioning
confidence: 57%
“…39 Cronbach's alpha for the full scale was 0.89 for the general population. 47 In a study of first year medical students the mean score was 80 (SD=9) 40 and the population norm has been reported as 80.4. 47 The Perceived Stress Scale (hereafter referred to as the "stress scale") is the most widely used psychological instrument for measuring the perception of stress.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…For example, research involving Chinese (Peng et al, 2012), Canadian (Rahimi et al, 2014), and U.S. (Houpy et al, 2017) medical students found male students as having statistically higher resilience scores than females. Whereas, Elizondo-Omaña et al (2010) did not observe such differences in resilience scores by gender in Mexican medical students. For medical educators, Porter and colleagues (2018) found no associations between the resilience level of U.S. family medicine programme directors and their demographic background, including gender.…”
Section: Introductioncontrasting
confidence: 57%